Characteristics of Nitrogen Removal and Extracellular Polymeric Substances of a Novel Salt-Tolerant Denitrifying Bacterium, Pseudomonas sp. DN-23 - Dan Li (Frontiers in Microbiology, 2020)
Extracellular polymeric substances (EPS) influence the auto-aggregation performance of cells and play an important role in nitrogen removal during wastewater treatment. In this study, a salt-tolerant aerobic denitrifying bacterium was isolated from tannery wastewater and identified as Pseudomonas sp. DN-23. The strain exhibited significant growth and denitrifying performance, with NaCl contents ranging from 0 to 50 g/L, and high antioxidative enzyme activity, especially that of catalase (CAT), was detected under salt stress. Even greater auto-aggregation ability was observed with elevated NaCl content. Extinction-emission matrix (EEM) and Fourier-transform infrared (FTIR) spectrum analyses showed that the main components of EPS were proteins and polysaccharides. The polysaccharide content was almost unaffected by NaCl stress, while the protein content increased with NaCl stress, and the proteins may play a more important role in auto-aggregation. Analysis of the contents of each protein’s secondary structure suggested that β-Sheets increased with increasing NaCl content, which may be related to the increase of auto-aggregation ability in response to NaCl stress. Therefore, NaCl stress increased the auto-aggregation performance by altering the compositions of EPS and the distribution of protein secondary structures. This study provided further insight into the denitrifying performance, and the relationship between aggregation ability and EPS characteristics under NaCl stress.